2016
DOI: 10.1017/s1751731115002815
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-breed reaction norm animal model accounting for robustness and heteroskedastic in a Nelore–Angus crossed population

Abstract: Our objective was to genetically characterize post-weaning weight gain (PWG), over a 345-day period after weaning, of Brangus-Ibagé (Nelore × Angus) cattle. Records (n = 4016) were from the foundation herd of the Embrapa South Livestock Center. A Bayesian approach was used to assess genotype by environment (G × E) interaction and to identify a suitable model for the estimation of genetic parameters and use in genetic evaluation. A robust and heteroscedastic reaction norm multiple-breed animal model was propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, the genetic correlation between intercept and slope was positive and of high magnitude for both traits, indicating that animals with higher intercept (average breeding value) respond more when the environmental conditions become less restrictive. Some studies indicated that a high correlation between intercept and slope suggests the occurrence of animals re‐ranking when evaluated in different environments (Su et al ; Oliveira et al ; Zhang et al ). Oliveira et al () observed that this occurs by scale effect in the EBV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the genetic correlation between intercept and slope was positive and of high magnitude for both traits, indicating that animals with higher intercept (average breeding value) respond more when the environmental conditions become less restrictive. Some studies indicated that a high correlation between intercept and slope suggests the occurrence of animals re‐ranking when evaluated in different environments (Su et al ; Oliveira et al ; Zhang et al ). Oliveira et al () observed that this occurs by scale effect in the EBV.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies indicated that a high correlation between intercept and slope suggests the occurrence of animals re-ranking when evaluated in different environments (Su et al 2006;Oliveira et al 2016;Zhang et al 2019). Oliveira et al (2016) observed that this occurs by scale effect in the EBV. The correlation estimate between intercept and slope was similar to that observed by Santana et al (2018) in Nellore cattle for HP (0.65) and higher than those reported by Santana et al (2013Santana et al ( , 2015 for SC of 0.001 and 0.14 respectively.…”
Section: (Co)variance Componentsmentioning
confidence: 99%